Crystal structure of type II NADH:quinone oxidoreductase from Caldalkalibacillus thermarum with an improved resolution of 2.15 Å. Issue 10 (10th October 2017) - Nakatani, Yoshio; Jiao, Wanting; Aragão, David; Shimaki, Yosuke; Petri, Jessica; Parker, Emily J.; Cook, Gregory M.
Abstract : The highest resolution structure of bacterial type II NADH:quinone oxidoreductase was determined at 2.15 Å resolution. This structure was used for in silico quinone substrate‐docking studies to investigate the binding poses of menadione and ubiquinone molecules. Abstract : Type II NADH:quinone oxidoreductase (NDH‐2) is a respiratory enzyme found in the electron‐transport chain of many species, with the exception of mammals. It is a 40–70 kDa single‐subunit monotopic membrane protein that catalyses the oxidation of NADH and the reduction of quinone molecules via the cofactor FAD. NDH‐2 is a promising new target for drug development given its essential role in many bacterial species and intracellular parasites. Only two bacterial NDH‐2 structures have been reported and these structures are at moderate resolution (2.3–2.5 Å). In this communication, a new crystallization platform is reported that produced high‐quality NDH‐2 crystals that diffracted to high resolution (2.15 Å). The high‐resolution NDH‐2 structure was used for in silico quinone substrate‐docking studies to investigate the binding poses of menadione and ubiquinone molecules. These studies revealed that a very limited number of molecular interactions occur at the quinone‐binding site of NDH‐2. Given that the conformation of the active site is well defined, this high‐resolution structure is potentially suitable for in silico inhibitor‐compound screening and ligand‐docking applications.